Effect of Compositionally Different Substrates on Elemental Properties of Bay Bolete Mushrooms: Case Study of 34 Essential and Non-essential Elements from Six Areas Affected Differently by Industrial Pollution - Andronikov, Alexandre V; Andronikova, Irina E; Sebek, Ondrej; Martinkova, Eva; Stepanova, Marketa; Perehon, Oksana (Biological trace element research, 2025)
We studied concentrations of 34 essential and non-essential elements in samples of edible Bay Bolete (Imleria badia) mushrooms added by samples of the growing substrate and bioavailable fraction. The samples were collected from six forested sites affected differently by industrial pollution and underlain by compositionally contrasting bedrock: granite, amphibolite, and peridotite. In all cases, mushrooms behaved as a bioconcentrating system for elements such as Ag, K, P, Rb, S, and Se (BCF > 1) being a bioexcluding system for the rest of the elements analyzed (BCF < 1). Most analyzed elements displayed moderate to high within-mushroom mobility being accumulated preferably in the apical parts of the mushroom's fruiting body (TF > 1). The highest mobility was demonstrated by Cd and Cu. Sodium was the only element with significantly low mobility (TF < 1), and it accumulated preferably in the stipe. Imleria badia seems to be sensitive to the accumulation of elements such as As, Cd, and Pb from the atmospheric deposits. Specific geochemistry of the growing substrate was reflected to different extend in the accumulation of elements such as Ag, Cu, Rb, S, Al, Ca, Fe, Ba, and Na in the mushroom's fruiting bodies.
Keywords: Mushroom; Translocation; Trace Elements; Environmental Monitoring; Agaricales; Uptake; Bedrock; Trace elements; stopové prvky; monitorování životního prostředí; Soil